ECG and morphologic adaptations in Arabic athletes: are the European Society of Cardiology's recommendations for the interpretation of the 12-lead ECG appropriate for this ethnicity?. Issue 15 (5th April 2013) - Riding, Nathan R; Salah, Othman; Sharma, Sanjay; Carré, François; George, Keith P; Farooq, Abdulaziz; Hamilton, Bruce; Chalabi, Hakim; Whyte, Gregory P; Wilson, Mathew G
Abstract : Aims: To examine the cardiac structure and function of Arabic athletes and to establish if the European Society of Cardiology (ESC) guidelines for the interpretation of an athlete's ECG are applicable to this ethnicity. Methods: 600 high-level Arabic, 415 Black African, 160 Caucasian male athletes (exercising ≥6 h/week) and 201 Arabic controls presented for ECG and echocardiographic screening. Results: 9 athletes (0.7%) were identified with a cardiac pathology associated with sudden cardiac death. Two Arabics (0.3%) and five Black Africans (1.2%) were diagnosed with hypertrophic cardiomyopathy; a prevalence four times greater in Black African compared to Arabic athletes. Arabic athletes had significantly greater (p<0.05) left ventricular (LV) end-diastolic diameters, maximal LV wall thicknesses and LV mass compared with controls; yet were significantly smaller than Black African and Caucasian athletes. The percentage of athletes demonstrating LV hypertrophy (≥12 mm) was comparable between Arabic, Black African and Caucasian populations (0.5%, 0.5% and 0.6%, respectively). There was no difference in the frequency of an uncommon and training-unrelated ECG between Arabic and Caucasian. However, Black Africans demonstrated a significantly greater prevalence than Arabic and Caucasian athletes (20% vs 8.4% and 6.9%, p<0.001); specifically more right/left atrial enlargement and T wave inversion. Conclusions: Arabic athletes present significantly smaller cardiac dimensions than Black African and Caucasian athletes. There was no significant difference between the frequency of an uncommon and training-unrelated ECG between Arabic and Caucasian athletes. Therefore, the use of ESC guidelines for the interpretation of an athlete's ECG is clinically relevant and acceptable for use within Arabic athletes.